Development of animation media in citizenship education learning based on HOTS - Elma Tiana; Zaka Hadikusuma Ramadan (Himpunan Pengembang Kurikulum Indonesia, 2025)
Rapid technological advances, demand innovation in teaching methods and learning media to improve student engagement and learning outcomes. This research aims to develop learning media in the form of animated videos to improve the learning experience and the effectiveness of learning in the classroom. The main reason for this research is the need for interactive and visually appealing teaching materials, which are in accordance with the characteristics of students and technological developments. This research uses ADDIE (Analysis, Design, Development, Implementation, and Evaluation) method. Products in the form of animated video learning media are validated by media experts, material experts, and linguists. The validation results showed an average score that was categorized as good. Media experts give